2012
DOI: 10.1111/j.1601-5037.2012.00553.x
|View full text |Cite
|
Sign up to set email alerts
|

Gingivitis and plaque scores of 8‐ to 11‐year‐old Burmese children following participation in a 2‐year school‐based toothbrushing programme

Abstract: The present study did not reveal a statistically significant effect of daily SBTB programmes in 8- to 11-year-old school children with respect to gingivitis and plaque scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 23 publications
1
6
0
5
Order By: Relevance
“…The reductions of scores were comparable between chewing stick and toothbrush users [ 30 ]. One quasi-experimental study in Burma found that a school-based tooth-brushing programme had no significant effects on plaque and bleeding scores [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The reductions of scores were comparable between chewing stick and toothbrush users [ 30 ]. One quasi-experimental study in Burma found that a school-based tooth-brushing programme had no significant effects on plaque and bleeding scores [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…The positive impacts of tooth-brushing activities were well-demonstrated [ 30 , 31 , 33 ], except for a study in Myanmar that found no impacts following the programme. It was suggested that the factors behind these findings might be the teachers’ lack of skills in giving the instructions as they were not dental professionals, the fact that instructing some groups of young children were not that effective, and children under ten years’ lack of ability to brush [ 32 ]. Another type of intervention was a SOC-based intervention, which was found to improve OHRQoL, SOC [ 35 , 36 ], gingival health, and oral health beliefs [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gingivitis is the most prevalent condition affecting the periodontium in pediatric patients (1,2). This highly prevalent disease among children and young adults results from the interplay between bacterial virulence factors and the host's limited defense capacity (3).…”
Section: Introductionmentioning
confidence: 99%
“…O estudo de aspectos relacionados à saúde bucal entre indivíduos com 12 anos é especialmente importante, pois este grupo etário foi escolhido pela OMS como a idade de monitoramento global da cárie dentária, principal agravo de saúde bucal em termos de prevalência, para comparações internacionais e acompanhamento das tendências da doença 4 . No entanto, sabe-se que, para controle e prevenção de alguns problemas bucais, tais como cárie e doença periodontal, é essencial a adesão a comportamentos adequados de higiene bucal 5,6 . Portanto, considerando-se o fato de que crianças com 12 anos estão, em sua maioria, inseridas no ambiente escolar, a escola parece ser um ambiente educacional e social propício para se trabalhar conhecimentos e mudanças de comportamento 7 .…”
Section: Introductionunclassified